2019
DOI: 10.3390/app9214673
|View full text |Cite
|
Sign up to set email alerts
|

A Multiscale Flow-Focused Geographically Weighted Regression Modelling Approach and Its Application for Transport Flows on Expressways

Abstract: Scale is a fundamental geographical concept and its role in different geographical contexts has been widely documented. The increasing availability of transport mobility data, in the form of big datasets, enables further incorporation of spatial dependencies and non-stationarity into spatial interaction modeling of transport flows. In this paper a newly developed multiscale flow-focused geographically weighted regression (MFGWR) approach has been applied, in addition to global and local Moran I indices of flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…As a dynamic and spatial process, urbanisation has been remarkably driven by continuous migration and transport flows between cities and provinces. As a result, with data sets of energy flows between provinces and cities, it will be meaningful to explore energy flow efficiency and its interactions with urbanisation development using the spatial statistical methods by Zhang et al (2019).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…As a dynamic and spatial process, urbanisation has been remarkably driven by continuous migration and transport flows between cities and provinces. As a result, with data sets of energy flows between provinces and cities, it will be meaningful to explore energy flow efficiency and its interactions with urbanisation development using the spatial statistical methods by Zhang et al (2019).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…(1) constructing a city-to-city transportation accessibility network based on the railway station and route data; (2) constructing a city-to-city population flow trend network by integrating wage and housing price data based on the transportation accessibility network; and (3) constructing a city-to-city technology innovation flow trend network by integrating urban technology innovation level based on the population flow trend network. The third part consists of two stages: (1) integrating the transportation accessibility network, population flow trend network, and technology flow trend network to construct an interaction weight coefficient matrix for cities; and (2) incorporating the weight coefficient matrix from (1) into the geographically weighted regression model to construct a spatial interaction regression model to study the influencing factors and mechanism of urban industrial agglomeration [46][47][48]. The framework of this study is shown in Figure 1.…”
Section: Overview Of Study Area and Experiments Data Preprocessingmentioning
confidence: 99%
“…The finding enhances the importance of the spatially heterogeneous effect compared to a global model [ 46 ]. Zhang et al [ 47 ] used a multi-scale geographically weighted regression model to examine the spatial interaction of expressway transport flows in Jiangsu Province, China. It illustrates the spatial effects at varied scales between push and pull forces of express trips at a regional scale.…”
Section: Literature Reviewmentioning
confidence: 99%